Nivel de satisfacción del usuario externo en consultorios externos del Hospital Distrital II-1 Santa Isabel – El Porvenir en Febrero del 2020 - Vertiz Cerna, Mark Anthony (2021)
The present study aimed to determine the level of satisfaction of the external user in external departments of Hospital Distrital II-1 Santa Isabel in Trujillo, La Libertad, in February 2020. Materials and Methods: Qualitative, descriptive, cross-sectional design. The modified SERVQUAL survey was applied, which measures the satisfaction of external users, with prior informed consent. There was a sample size of 325 patients and/or companions. The data processing was carried out according to the satisfaction rank. Results: 61.92% of the external users were satisfied with the care received in the external clinics. The reliability dimension had a satisfaction level of 54.72%. The response capacity dimension had a satisfaction level of 59.54%. The security dimension had a satisfaction level of 68.62%. The empathy dimension had a satisfaction level of 73.48%. The tangible aspects dimension had a satisfaction level of 52.15%. The question with the highest satisfaction was P18 (77.5%), in relation to the understandability of the doctor's explanation, and the question with the least satisfaction was P22 (64%), in relation to the cleanliness and comfort of the waiting room. Conclusion: The patients who were seen in the outpatient clinics of the Hospital Distrital II-1 Santa Isabel in February 2020 present a level of satisfaction greater than 60%, which according to the modified SERVQUAL methodology of the MINSA technical guide, corresponds to the range “acceptable”.